NEW RELIABILITY SCORE FOR COMPONENT STRENGTH USING KULLBACK-LEIBLER DIVERGENCE - Gokdere, Gokhan; Gurcan, Mehmet (Polish Maintenance Soc, 2016)
The reliability of technical systems is one of the most important research subjects in the point reached by modern science. In many recent studies, this problem is solved by evaluation the operation performance of determined one or more components operating under stress. At this point, R=P(X
Nowa metoda oceny niezawodno?ci na podstawie wytrzyma?o?ci elementów z zastosowaniem dywergencji Kullbacka-Leiblera
Keywords: reliability; stress-strength model; multistate system model; Kullback-Leibler divergence